Improving Access to Refractive Services in Adults: A Health Examination Center-Based Model - Lin, Haishuang; Sun, Jing; Congdon, Nathan; Xu, Meiping; Liu, Shanshan; Liang, Yuanbo; Wang, Hailin; Zhang, Shaodan (Frontiers in Medicine, 2021)
Purpose: To assess the potential of a health examination center-based screening model in improving service for uncorrected refractive error. Methods: Individuals aged>=18 undergoing routine physical examinations at a tertiary hospital in the northeast China were invited. Presenting visual acuity, non-cycloplegic autorefraction, non-contact tonometry, fundus photography and slit-lamp examination were performed. Refractive error was defined as having spherical equivalent<= -0.75 D or >=+1D, and uncorrected refractive error was considered as refractive error combined with presenting visual acuity < 6/12 in better eye. Costs for the screening were assessed. Results: A total of 5284 participants (61±14 years) were included. The overall prevalence of myopia and hyperopia was 38.7% and 23.5%, respectively. The prevalence of uncorrected refractive error was 7.85%. Women (P<0.001 and P=0.003), those with age>= 70 (P<0.001 and P=0.003) and myopia(P＜0.001 and P＜0.001) were at higher risk of uncorrected refractive error and uncorrected refractive error-related visual impairment. Spectacle coverage rate was 70.6%. The cost to identify a single case of refractive error and uncorrected refractive error was US3.2 and US25.2, respectively. Conclusions: The prevalence of uncorrected refractive error is high in urban Chinese adults. Health examination center-based refractive error screening provide efficient and low-cost model to improve refractive services in China.